A method for accurate pH mapping with chemical exchange saturation transfer (CEST) MRI - Sun, Phillip Zhe (Contrast Media Mol Imaging, 2015)
Chemical exchange saturation transfer (CEST) MRI holds enormous promise for imaging pH. Whereas the routine CEST-weighted MRI contrast is complex and susceptible to confounding factors such as labile proton ratio, chemical shift, bulk water relaxation and RF saturation, ratiometric CEST imaging simplifies pH determination. However, the conventional ratiometric CEST (RCEST) MRI approach is limited to CEST agents with multiple exchangeable groups. To address this limitation, RF power-based ratiometric CEST (PRCEST) imaging has been proposed that ratios CEST effects obtained under different RF power levels. Nevertheless, due to concomitant RF saturation (spillover) effect, the recently proposed PRCEST imaging is somewhat dependent on parameters including bulk water relaxation time and chemical shift. Herein we hypothesized that RF power-based ratiometric analysis of RF spillover effect-corrected inverse CEST asymmetry (PRICEST) provides enhanced pH measurement. The postulation was verified numerically, and validated experimentally using an in vitro phantom. Briefly, our study showed that the difference between MRI-determined pH (pH(MRI)) and electrode-measured pH being 0.12±0.13 and 0.04±0.03 for PRCEST and PRICEST imaging, respectively, and the newly proposed PRICEST imaging provides significantly more accurate pH determination than PRCEST imaging (P<0.01, Wilcoxon signed-rank test). Notably, the exchange rate shows dominantly base-catalyzed relationship with pH, independent of creatine concentration (P>0.10, Analysis of Covariance). In addition, the derived labile proton ratio linearly scales with creatine concentration (P<0.01, Pearson Regression). To summarize, PRICEST MRI provides concentration-independent pH imaging, augmenting prior quantitative CEST methods for accurate pH mapping.